Ischemic Preconditioning and Placebo Intervention Improves Resistance Exercise Performance. Issue 5 (May 2016) - Marocolo, Moacir; Willardson, Jeffrey M.; Marocolo, Isabela C.; Ribeiro da Mota, Gustavo; Simão, Roberto; Maior, Alex S.
Abstract : Abstract: Marocolo, M, Willardson, JM, Marocolo, IC, da Mota, GR, Simão, R, and Maior, AS. Ischemic preconditioning and PLACEBO intervention improves resistance exercise performance. J Strength Cond Res 30(5): 1462–1469, 2016—This study evaluated the effect of ischemic preconditioning (IPC) on resistance exercise performance in the lower limbs. Thirteen men participated in a randomized crossover design that involved 3 separate sessions (IPC, PLACEBO, and control). A 12-repetition maximum (12RM) load for the leg extension exercise was assessed through test and retest sessions before the first experimental session. The IPC session consisted of 4 cycles of 5 minutes of occlusion at 220 mm Hg of pressure alternated with 5 minutes of reperfusion at 0 mm Hg for a total of 40 minutes. The PLACEBO session consisted of 4 cycles of 5 minutes of cuff administration at 20 mm Hg of pressure alternated with 5 minutes of pseudo-reperfusion at 0 mm Hg for a total of 40 minutes. The occlusion and reperfusion phases were conducted alternately between the thighs, with subjects remaining seated. No ischemic pressure was applied during the control (CON) session and subjects sat passively for 40 minutes. Eight minutes after IPC, PLACEBO, or CON, subjects performed 3 repetition maximum sets of the leg extension (2-minute rest between sets) with the predetermined 12RM load. Four minutes after the third set for each condition, blood lactate was assessed. The results showed that for the first set, the number of repetitions significantly increased for both the IPC (13.08 ± 2.11; p = 0.0036) and PLACEBO (13.15 ± 0.88; p = 0.0016) conditions, but not for the CON (11.88 ± 1.07; p > 0.99) condition. In addition, the IPC and PLACEBO conditions resulted insignificantly greater repetitions vs. the CON condition on the first set ( p = 0.015; p = 0.007) and second set ( p = 0.011; p = 0.019), but not on the third set ( p = 0.68; p > 0.99). No difference ( p = 0.465) was found in the fatigue index and lactate concentration between conditions. These results indicate that IPC and PLACEBO IPC may have small beneficial effects on repetition performance over a CON condition. Owing to potential for greater discomfort associated with the IPC condition, it is suggested that ischemic preconditioning might be practiced gradually to assess tolerance and potential enhancements to exercise performance.